The Use of English Pop Song to Enhance Students’ Listening Ability - Sri Ariani; Khairi Iswandi (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2020)
This research aims to find out the use of English Pop Song to enhance students’ listening ability in the first grade of SMAN 10 Mataram in 2020/2021. The research method of this research used Classroom Action Research. The data in this research was taken based on the listening test. The subject of this research was first-grade students IPS 1 of SMAN 10 Mataram, which consisted of 25 students. This research was conducted in one cycle. The instruments of this research were taken by test and observation sheet. The main score of students listening ability of pre-test was 45 with a percentage (12%) and the main score of post-test was 76 with a percentage (84%). The researchers concluded that the score of the students’ listening was higher than the Minimum Complete Criteria Success (KKM). So it meant that the use of English Pop Song was significant to enhance students’ listening ability.